Quantification of myocardial iron deposition by two-dimensional speckle tracking in patients with β-thalassaemia major and Blackfan–Diamond anaemia. Issue 5 (4th February 2011) - Garceau, P; Nguyen, E T; Carasso, S; Ross, H; Pendergrast, J; Moravsky, G; Bruchal-Garbicz, B; Rakowski, H
Abstract : Background: Cardiac disease related to transfusional iron overload is the leading cause of death in patients with β-thalassaemia major. Early myocardial iron deposition predates decreased left ventricular dysfunction and currently is best assessed by cardiac magnetic resonance. Methods: Echocardiographic speckle tracking-derived myocardial mechanics were compared with cardiac MRI T2 star (T2*) calculations in 45 chronically transfused patients with β-thalassaemia major or Diamond–Blackfan anaemia (26 retrospectively and an additional 19 for validation). Two groups were studied: patients with presumed cardiac iron overload and interventricular T2* value ≤20 ms (low T2*) and patients with >20 ms (normal T2*). They were compared with a normal control group of 18 age- and gender-matched patients. Results: Patients with low T2* had a uniform decrease in longitudinal and circumferential strain compared with normal controls (−16±3% vs −20±3% and −20±4% vs −23±5%, respectively; p<0.0005). Peak twist and peak apical rotation were lower in patients with low T2* than in those with normal T2* or normal control patients. Conversely, no significant difference was observed between patients with normal T2* and controls. There was a strong and direct logarithmic correlation between average global longitudinal strain and T2* values (r=−0.68, p=0.0007). Using a cut-off of ≤−17%, global longitudinal strain predicted a T2* value of <20 ms with a sensitivity of 76% and a specificity of 88%. Conclusion: Myocardial mechanics offers a simple alternative to cardiac MRI for assessing significant myocardial iron deposition.